Sucrose favors Pseudomonas aeruginosa pellicle production through the extracytoplasmic function sigma factor SigX. Issue 2 (26th June 2014) - Bouffartigues, Emeline; Duchesne, Rachel; Bazire, Alexis; Simon, Marjolaine; Maillot, Olivier; Dufour, Alain; Feuilloley, Marc; Orange, Nicole; Chevalier, Sylvie
Abstract Pseudomonas aeruginosa biofilm formation was increased by addition of sucrose to Luria–Bertani medium, whereas addition of NaCl to a final similar osmolarity and use of maltose instead of sucrose, were ineffective. In a previous study, we showed that the extracytoplasmic sigma factor SigX is activated in the presence of sucrose. The sucrose‐mediated pellicle increase was abolished in a sigX mutant strain. Sucrose addition led to an increase in pel expression and cyclic‐diguanylate (c‐di‐GMP) pool level production. Interestingly, these two phenotypes were strongly decreased in a sigX mutant. Since pel is not known as a SigX‐target, we suspect SigX to be involved in the c‐di‐GMP production. We found that expression of the diguanylate cyclase PA4843 gene was increased in the presence of sucrose at least partly through SigX activity. Our study shows that sucrose itself rather than osmolarity favours the biofilm mode of P. aeruginosa through the activation of SigX.